Congruification: support for time scaling large phylogenetic trees. Issue 7 (29th April 2013) - Eastman, Jonathan M.; Harmon, Luke J.; Tank, David C.; Paradis, Emmanuel
Summary Approaches for efficient statistical estimation of large phylogenies are now available (Bioinformatics, 2006, 22, 2688), and yet we lack adequate tools for synthesizing information from previous analyses into large timetrees. Here, we present a cross‐platform r tool that integrates with tree of life efforts by mapping divergence times from an existing timetree (a 'reference') to another uncalibrated phylogeny (a 'target') that samples from the same lineage. Leveraging existing methods for rate‐smoothing phylograms, this tool enables the rapid generation of very large timetrees where direct estimation of the timing of lineage diversification is either impracticable or impossible. The primary output of the tool is to return divergence times for nodes resolved as concordant between the reference and target. Given the computed set of secondary calibrations, post hoc tree transformation can be accomplished using existing resources that assume either a strict or relaxed evolutionary clock. Our software is provided open source in the geiger package (http://cran.r-project.org/package=geiger) and is thoroughly demonstrated in the Supporting Information.